Various Ca/P ratios of thin calcium phosphate films - Lee, IS; Whang, CN; Kim, HE; Park, JC; Song, JH; Kim, SR (ELSEVIER SCIENCE BV, 2002)
Various Ca/P ratios of calcium phosphate films were formed by electron beam evaporation with and without simultaneous Ar ion bombardment. The Ca/P ratio of film was controlled by either using the evaporants having the different ratio of Ca/P with addition of CaO or increases in ion beam current. Without ion beam bombardments, the Ca/P ratio of film increased from 1.12 to 1.71 with addition of 25 wt.% CaO. The effect of ion beam assistance was also observed, and the ratio increased with ion beam current. The Ca/P ratio of the film was intimately related to the structure formed after heat treatment and the dissolution behavior. The films had the average bonding strength of 64.8 MPa that was much higher than the plasma sprayed hydroxyapatite coating layer. Calcium phosphate film showed beneficial effects on osteoblast cell attachment and proliferation. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: SPRAYED HYDROXYAPATITE COATINGS; HYDROXYLAPATITE; MICROSTRUCTURE; DEPOSITION; INTERFACE; TITANIUM; IMPLANTS; TISSUE